Tata Kelola Pemerintahan yang Berbasis Pengetahuan - Supriati, Arie (Universitas Brawijaya, Indonesia, 2014)
Reform has done this nation has not reached the expected goal as the increasing community welfare, especially the increase in community welfare at lower middle and bottom level. Bureaucratic reform, democratization, and governance reform is the implementation of correct policy. But the policy has been correctly it should be implemented by human resources that are reliable. As good as any policy that created the success in implementation is determined by the people who perform. For that we need an effort to improve the management of personnel resources include personnel recruitment, remuneration system, performance appraisal, training and development supported by a strong culture and leadership, thereby building a knowledge-based government that will be able to people welfare.